Advancing student research in education law - de Waal, Elda; Serfontein, Erika (South African Journal of Higher Education, 2016)
On the one hand, the popularity of education law for post graduate studies is calling for a reflection on a sound research approach that would complement both the boundaries of the law as substantive discipline and how people experience or view the law. On the other hand, such research requires knowledge of both the law and education. Two types of hands-on experiences have encouraged this article in an attempt to address the general lack of precise research methodologies and theoretical frameworks in order to advance student research in education law. Having (1) provided a fundamental background to law; (2) considered the aim of research and what it entails within law; (3) looked at legal versus other research; and (4) presented a brief historical perspective on South African legal research, an integrative multidisciplinary research approach is proposed in order to side-step being bogged down by conventional approaches that do not necessarily promote successful research outcomes. School level Catch 22's need solid education law research!